The Variation of G and Λ in Cosmology - Aroonkumar Beesham (Universe)
The idea of varying constants of nature is very old, and has commanded a lot of attention since first mooted. The variation in the gravitational parameter G and cosmological parameter <semantics>Λ</semantics> is still an active area of research. Since the idea of a varying G was introduced by Dirac almost a century ago, there are even theories that have variable G such as the Brans–Dicke theory and the scale covariant theory. Both these theories also have a varying <semantics>Λ</semantics> in their full generalisations. A varying <semantics>Λ</semantics> was also introduced around the same time as that of varying G. It is interesting to note that a possible solution to the cosmological constant problem can be realised from a dynamic <semantics>Λ</semantics>. In this work, we focus on a varying <semantics>Λ</semantics> and G framework. In almost all studies in the simplest framework of variables <semantics>Λ</semantics> and G, it is found that one of them has to increase with time. However, observations and theoretical considerations indicate that both <semantics>Λ</semantics> and G should decrease with time. In this paper, we propose a solution to this problem, finding theories in which both <semantics>Λ</semantics> and G decrease with time.